Report of the Special Committee on Harmful Effects of Pesticides - Planning Commission (Planning Commission, 1967)
The Report of the Special Committee on the Harmful Effects of Pesticides presents a detailed examination of the rapid expansion in pesticide use since the 1940s and its associated risks to human health, animals, and the environment. With the introduction of highly toxic synthetic chemicals such as organochlorine and organophosphorus compounds, pesticides became widely used in agriculture, public health, and industry, leading to concerns about acute toxicity, environmental persistence, and bioaccumulation. The report highlights incidents of poisoning affecting humans, livestock, fish, and wildlife, often resulting from misuse, inadequate storage, poor labeling, and lack of awareness, thereby underscoring the need for stricter safety and regulatory measures. Drawing on international studies and experiences from countries like the United States and Great Britain, as well as notable cases in India such as the Kerala food poisoning incident, the Committee emphasizes the importance of legislation, including the Insecticides Bill of 1964, to regulate the manufacture, import, distribution, and application of pesticides. It also discusses the growing public concern about environmental and health hazards, notably influenced by Rachel Carson’s work, and calls for continuous review of pesticide usage by technical bodies. The report further situates pesticide use within the broader Indian context, describing the country’s diverse agricultural landscape, pest-related crop losses, and reliance on chemical control methods to protect food production, forestry, livestock, and public health initiatives such as malaria eradication. While acknowledging the essential role of pesticides in reducing economic losses and controlling disease vectors, the Committee advocates for balanced approaches, including research into safer alternatives like biological control, improved safety practices, and stronger institutional frameworks. Overall, the report underscores the dual challenge of maximizing agricultural productivity and public health benefits while minimizing the harmful effects of pesticide use through scientific regulation and informed policy intervention.
Indian Council of Agricultural research
Indian Council of Agricultural research
Keywords: Pesticides, Environmental Toxicity, Human Health Risks, Wildlife Impact, Agricultural Practices, Chemical Regulation, Food Contamination, Public Health, Pest Control, Biological Control, Insecticides Bill 1964, Malaria Control